Palu (Sulawesi): Problematik der Landnutzung in einem klimatsichen Trockental am Äquator - Metzner, Joachim (ERDKUNDE, 1981)
Palu, located less than one degree south of the equator on the island of Sulawesi (Celebes), has the lowest rainfall recorded in the Malay Archipelago. Looking at Palu' s dry grass-savannas with their scattered cactus thickets the visitor finds it hard to believe that he is in Central Sulawesi, a province which is known for its dense tropical forest. This peculiarity, which is due to the preponderance of local wind systems over the monsoons, is conditioned by high chains of mountains that flank the Palu valley on either side. An extremely low and erratic rainfall regime enhanced by highly unstable geomorphological conditions make the utilization of the rather fertile valley floor a gamble. In fact, by trying to overcome these difficulties through irrigated agriculture, man has decisively contributed to upset the valley's delicate ecological conditions and has thereby set in motion a spiral of environmental deterioration. As a result of uncontrolled I a dang cultivation in the mountains the irrigation of paddyfields in the valley was seriously impaired. On the abandoned sawahs a pioneer plant from South America (Opuntia nigricans) spread unchecked in the valley's dry northern portion and within a short period also forced the farmers to give up valuable pasture and farming land. Only in the thirties did the government succeed in keeping this pest at bay through the application of entomological means.